Administrative Mechanism for Issuing Legal Products in the Legal Section of the Regional Secretariat of North Bolaang Mongondow Regency - Risna Gumohung (PT FORMOSA CENDEKIA GLOBAL, 2022)
This type of research is descriptive research, with a qualitative approach. This study aims to determine the administrative mechanism for issuing legal products in the Legal Department of the Regional Secretariat of North Bolaang Mongondow Regency. The focus of the problem is File Submission, Registration/Numbering, Coordination Flow. The results of this study indicate that the Legal Section of the Regional Secretariat of North Bolaang Mongondow Regency regarding the Administrative Mechanism of Issuing Legal Products has not run optimally, where there are problems such as Submission of Regional Legal Product Files because there are still many Employees from Regional Work Units who do not understand what are the requirements in submitting legal products areas, registration or numbering of legal products still uses a manual system, is still recorded in the agenda book, and the flow of coordination has not gone well in accordance with the Standard Operating Procedures for the Legal Department, resulting in scattered or missing legal products to be signed by the regional leadership.